Care managers’ experiences in a collaborative care program for high risk mothers with depression - Huang, Hsiang (2012)
OBJECTIVES: The aim of this study is to understand care managers’ experiences in caring for depressed mothers in an integrated behavioral health program. METHODS: As part of a quality improvement project, we conducted a focus group interview with six care managers caring for low income mothers with behavioral health needs in a safety net program in King County, WA. Using thematic analysis, codes were organized into themes that describe the care managers’ experiences. RESULTS: Two organizing themes along with associated themes emerged: 1) Assets for improving depression outcomes: patient-provider interactions including the importance of engagement; program resources such as care coordination and access to a consulting psychiatrist and 2) Barriers to improved depression outcomes: patient-provider interactions including difficulty engaging patient; patient-related factors such as multiple stressors; program resources such as need for more psychiatric support; and difficulty accessing outside resources. CONCLUSIONS: Numerous potentially modifiable factors including levels of engagement, motivational interviewing, and increased psychiatric support were identified by care managers as affecting depression care and outcomes. Implications for care management training and approaches to psychiatric consultations are discussed.